Acts and texts : performance and ritual in the Middle Ages and the Renaissance - Postlewate, Laurie, 1957-; Hüsken, Wim N. M. (Amsterdam ; New York, NY : Rodopi, 2007)
For the Middle Ages and Renaissance, meaning and power were created and propagated through public performance. Processions, coronations, speeches, trials, and executions are all types of public performance that were both acts and texts: acts that originated in the texts that gave them their ideological grounding; texts that bring to us today a trace of their actual performance. Literature, as well, was for the pre-modern public a type of performance: throughout the medieval and early modern periods we see a constant tension and negotiation between the oral/aural delivery of the literary work a.
The preacher and his audience: Dominican conceptions of the self in the thirteenth century / Dallas G. Denery II -- Public-access patronage: book-presentation from the crowd at a royal presentation / Joyce Coleman -- Eternal Rome and Cola di Rienzo's show of power / Amy Schwarz -- Diversity in unity: Elizabeth's coronation procession / L. Caitlin Jorgensen -- On cushions and chairs: the ritual contruction [sic] of authority in New Spain / Alejandro Cañeque -- Talking pictures: performance on th epage / Adrian P. Tudor -- Medieval literary performance: Gautier de Coinci's Guide for the Perplexed / Kathryn A. Duys -- Privatizing the Conte du Graal: how renaissance printers reformatted Chrétien's public text for private reading / Paul Creamer -- A contract for an early festival book: Sarrasin's Le Roman du Hem (1278) / Nancy Freeman Regalado -- Death slips onto the renaissance stage: Morris dancing, mimed Moors, and nascent rituals in Fletcher and Shakespeare / William E. Engel -- Experimenting with the performance of medieval narrative / Evelyn Birge Vitz & Linda Marie Zaerr -- Ysuet's legacy: women writers and performers in the medieval French romance Ysaÿe le triste / Marilyn Lawrence -- 'A bawdy lecture unto ladies': music speeches at early-modern Oxford / Felicity Henderson.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Literature, Medieval -- History and criticism; Literature, Modern -- 15th and 16th centuries -- History and criticism; Littérature médiévale -- Histoire et critique; Littérature -- 15e et 16e siècles -- Histoire et critique; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Literature, Medieval; Literature, Modern; 1400-1599; Criticism, interpretation, etc